Action Research by Academic Community to Tackle Teenager's Problems in the Modern Information Age: Implementation of Science through the Community Service Program - Benny Munardi; Muhammad Julfahmi Nasution; Irham Dongoran (ASSUNNAH PRESS, 2022)
Many complaints from parents, educators, and the public regarding the behavior of teenagers that are difficult to control, naughty, stubborn, deviant behavior, and others. This problem also occurs in Bulu Bargut Village, Marbao, North Labuhan Batu, North Sumatra. Therefore, community service programs are used as a solution to solve juvenile delinquency by directing them to useful activities. This community service uses the Participatory Action Research (PAR) method, by being directly involved in extracting diverse information, then taking action as a solution to problems that have been identified, and by participating in building the design and implementation of actions based on research results. The basis for doing PAR is the need to get the desired changes. During the seventeen days of activities carried out, it has succeeded in instilling the love of Al-Qur'an in teenagers. With the love of the Qur'an, it is hoped that they can stay away from and reduce the existence of useless activities during the month of Ramadan such as wild racing playing social media, and games. Then the result of the community service program is that the community is enthusiastic to participate in the activities held such as training activities on the nature of the prophet's wudu, lectures before tarawih salat, Friday khatib, and iftar jama’i. So the program carried out is very effective in overcoming and handling juvenile delinquency in Pulo Bargot Village through intensive learning of the Qur'an and teaching Islamic morals. Then what is more important is that the community support is very positive in receiving this program. Likewise, teenagers are very enthusiastic about memorizing the Qur'an and participating in programs implemented during community service programs.